Case Report: A Rare Case of Fourth Ventricle to Spinal Subarachnoid Space Shunt Migration: Surgical Pearl and Literature Review - Serratrice, Nicolas; Faddoul, Joe; Tarabay, Bilal; Taifour, Sarkis; Abi Lahoud, Georges Naïm (Frontiers in Surgery, 2021)
Background: In the event of syringomyelia communicating with the fourth ventricle, a fourth ventricle to cervical subarachnoid space shunting could be proposed. Case report: In this article, we describe the case of a 40 years-old woman who had a previously implanted fourth ventricle to spinal subarachnoid space shunt for the treatment of syringomyelia in a context of Chiari syndrome. The catheter migrated intradurally to the lumbosacral space, but in the absence of neurological repercussions, we decided to leave it in place. Conclusions: To the best of our knowledge this is the first case described in the literature of a catheter migration in the subarachnoid space from occipito-cervical to lumbo-sacral level.